EFISIENSI PENGGUNAN MODAL KERJA PADA PERUSAHAAN MEUBEL SEYLA - LCA Robin Jonathan (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
Research objectives are to: (1) measure the efficient use of working capital at a company, (2) know the amount of working capital used in a company, and (3) shows good and correct financial management.The research was conducted for 3 months at a furniture business in the company "SEYLA" in the city of Samarinda.Data collection methods in the study include: documentation of the collection of data by copying the documents of the company and the research literature.  Data analysis was performed using the method of working capital turnover.The results showed that: (1) in 2010, net working capital is used for Rp. 798,850,000,- and is able to generate net sales of Rp. 800,000,000,- giving rise to the velocity of 1.00 times as much working capital; (2) Net working capital turnover in 2011 as much as 0.77 times. In 2010, net working capital is used as much as Rp. 1,098,850,000,- and is able to generate net sales of Rp 850,000,000,-; (3) Net Working Capital Turnover in 2011 as much as 0.77 times while the Net Working Capital Turnover in 2010, as much as 1.00 times. Working capital turnover rate indicates that a decline in working capital turnover of 0.23 times in the 2011; and (4) there was an inefficiency in the use of net working capital in the company SEYLA in 2011. It rejected the hypothesis that there is efficient use of working capital to the company SEYLA.